Flexible Frequency-Band Reallocation Networks Using Variable Oversampled Complex-Modulated Filter Banks. (8th November 2006) - Johansson Johansson, Håkan Håkan; Löwenborg Löwenborg, Per Per
Abstract : A crucial issue in the next-generation satellite-based communication systems is the satellite on-board reallocation of information which requires digital flexible frequency-band reallocation (FBR) networks. This paper introduces a new class of flexible FBR networks based on variable oversampled complex-modulated filter banks (FBs). The new class can outperform the previously existing ones when all the aspects flexibility, low complexity and inherent parallelism, near-perfect frequency-band reallocation, and simplicity are considered simultaneously.